Analysis of The Efficiency of Sharia Commercial Banks in Indonesia Using a Two-Stage Data Envelopment Analysis Approach - marhamah; Sarbullah; Dewi Sri Handayani (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2024)
This research aims to analyze the efficiency of 10 Islamic banks in Indonesia, as well as analyze the influence of bank size, ROA, NPF, FDR and inflation on the efficiency level of Sharia Commercial Banks. The samples in this research is 10 Sharia Commercial Banks that met the criteria. The research observation period is 2019-2023. The analysis technique for this research uses DEAP 2.1 in the first stage and tobit regression in the second stage. The research results show that the sharia commercial banks assuming an intermediation approach during 2019-2023 is still categorized as inefficient, because the average efficiency value of sharia commercial banks is around 80% or still below 1. The results of the tobit regression analysis show size bank, ROA and FDR have a positive and significant effect on the efficiency level of Sharia Commercial Banks, while NPF and Inflation do not have a significant effect on the efficiency level of Sharia Commercial Banks. The research implications be used by regulators to develop effective policies in supporting the growth and stability of the sharia banking sector. In addition, these findings also provide investors with insight into the relative performance of Islamic banks, and making more informed investment decisions. Abstrak - Penelitian ini bertujuan untuk menganalisis efisiensi 10 perbankan syariah di Indonesia 2019-2023, serta menganalisis pengaruh ukuran bank, ROA, NPF, FDR dan inflasi terhadap tingkat efisiensi Bank Umum Syariah. Sampel dalam penelitian ini adalah 10 Bank Umum Syariah yang memenuhi kriteria. Periode observasi penelitian adalah tahun 2019-2023. Teknik analisis penelitian ini menggunakan DEAP 2.1 ditahap pertama dan regresi tobit ditahap kedua. Hasil penelitian menunjukkan bahwa efisiensi Bank Umum Syariah dengan asumsi pendekatan intermediasi selama 2019-2023 masih dikategorikan inefisien, dikarenakan rata-rata nilai efisiensi Bank Umum Syariah berkisar diangka 80% atau masih dibawah angka 1. Hasil analisis regresi tobit menunjukkan ukuran bank, ROA dan FDR berpengaruh positif dan signifikan terhadap tingkat efisiensi Bank Umum Syariah, sedangkan NPF dan inflasi tidak berpengaruh signifikan terhadap tingkat efisiensi Bank Umum Syariah. Implikasi penelitian digunakan oleh regulator untuk menyusun kebijakan yang efektif dalam mendukung pertumbuhan dan stabilitas sektor perbankan syariah. Selain itu, temuan ini juga memberikan wawasan bagi investor tentang kinerja relatif bank syariah, membuat keputusan investasi yang lebih terinformasi.